Pencegahan Keluarga Pasien Kanker Terhadap Paparan Obat Kemoterapi - Rani Lisa Indra; Hayyu Mufathuzzahra; Meisa Daniati (Jurnal Kesehatan Komunitas, 2022)
Cytotoxic drugs not only affected cancer patients receiving chemotherapy but also family members who come into close contact with the patient either during treatment or after the patient is at home. The aim of this study was to identify prevention taken by the patient's family to avoid exposure to chemotherapy drugs after the patient arrived home. This study was descriptive with a sample of 84 families of cancer patients undergoing chemotherapy, who were taken by consecutive sampling technique. Data collection using a questionnaire and processing was carried out univariately using a frequency distribution. The results showed that 58.3% of patients did not live in one house with children, pregnant women, and the elderly; 39.3% of families used different toilets from patients; 85.7% of families flushed the toilet using toilet cleaning fluid after being used by the patient; 78.6% of families replaced mattress pads at least once in 3 days, 70.2% of families used disposable gloves to handle contaminated clothing by patient excretions and 84.5% of families provide a special vomitus place. It is hoped that the nurses will educate patients and their families on how to prevent exposure to chemotherapy drugs at home.